ExStroke Pilot Trial of the effect of repeated instructions to improve physical activity after ischaemic stroke: a multinational randomised controlled clinical trial. (22nd July 2009) - Boysen, Gudrun; Krarup, Lars-Henrik; Zeng, Xianrong; Oskedra, Adam; Kõrv, Janika; Andersen, Grethe; Gluud, Christian; Pedersen, Anders; Lindahl, Marianne; Hansen, Lotte; Winkel, Per; Truelsen, Thomas
Abstract : Objectives To investigate if repeated verbal instructions about physical activity to patients with ischaemic stroke could increase long term physical activity. Design Multicentre, multinational, randomised clinical trial with masked outcome assessment. Setting Stroke units in Denmark, China, Poland, and Estonia. Participants 314 patients with ischaemic stroke aged ≥40 years who were able to walk—157 (mean age 69.7 years) randomised to the intervention, 157 (mean age 69.4 years) in the control group. Interventions Patients randomised to the intervention were instructed in a detailed training programme before discharge and at five follow-up visits during 24 months. Control patients had follow-up visits with the same frequency but without instructions in physical activity. Main outcome measures Physical activity assessed with the Physical Activity Scale for the Elderly (PASE) at each visit. Secondary outcomes were clinical events. Results The estimated mean PASE scores were 69.1 in the intervention group and 64.0 in the control group (difference 5.0 (95% confidence interval −5.8 to 15.9), P=0.36. The intervention had no significant effect on mortality, recurrent stroke, myocardial infarction, or falls and fractures. Conclusion Repeated encouragement and verbal instruction in being physically active did not lead to a significant increase in physical activity measured by the PASE score. More intensive strategies seem to be needed to promote physical activity after ischaemic stroke. Trial registration Clinical Trials NCT00132483